(untitled) (lectio difficilior, 2020)
In this article, I analyse two critical situations for women that potentially prompt women to commit suicide. Both situations are linked to the loss of integrity of body. The first situation is violation or in broader terms, extramarital sex, the second situation is in war, the siege and capture of a city. I compare texts of the Hebrew Bible with archaic Greek literature. I find characteristic differences in handling these topics between texts of the Hebrew Bible and archaic Greek literature. • Extramarital sex: This is a problem in texts of the Hebrew Bible; if violence is involved as in the case of Dina (Genesis 34), the concubine of the Levite (Judges 19) or Tamar (2 Samuel 13,1–22), the outcome was devastating for all, for the wrongdoer, his victim, and the families and tribes of both. In archaic Greek literature we find some hints that extramarital sex was not in every case a social offence: We know of princesses of mythical times who were married and conceived a child of a God. An extraordinary case are Pitane and Euadne, mother and daughter, not married young women, who both became pregnant of a God. Euadne had some struggle to introduce her boy as a family member, finally, her son was ancestor of the well-known family of priests, the Iamids. • War or siege and capture of a city: The Hebrew Bible seems to allow women in this extraordinary case to kill the aggressor (Judges 9,50–56; 4,17–21) or, even better, to negotiate with the aggressor (2 Samuel 20,14–22). Women in Greek archaic literature are condemned to passivity. Only later sources know of the woman poet Telesilla (5. C. BCE) who organized the defence of her hometown Argos successfully.